Determining the subject balance in higher education : how should this be done? - Taylor, Jim [Verfasser] (My University, 1990)
"It is the U.K. Government's policy to achieve 'the right number and balance of graduates in the 1990s'. According to the Government, this will require more attention being paid to 'the needs of the economy' when decisions concerning the allocation of resources between subject areas are being made. In particular, the Government believes that higher education should be more vocationally-oriented and aims to influence the subject balance in this direction. The purpose of this paper is to examine the possibility of constructing a set of indicators for deciding which subjects have produced the most marketable and the most satisfied graduates. Two sets of indicators are constructed. The first is based on labour market indicators such as the earnings and unemployment rates of graduates. The second set of indicators is based upon information about the value which the graduates themselves place upon their degree qualifications. When these two sets of indicators were combined, substantial differences were found in the relative worth of graduates in different subjects (for male and female graduates separately). Graduates in some subjects achieved far higher scores than graduates in other subjects on either one or both sets of indicators." (author's abstract) ((en)) Der Beitrag prüft die Möglichkeit der Konstruktion eines Indikatorenbündels, das (der Hochschulpolitik und Hochschulplanung in Grossbritannien) Entscheidungshilfen für die Antwort auf die Frage liefert, welche Studienfächer die "marktfähigsten" und zufriedensten Absolventen hervorbrachten. Dazu wurden zwei Indikatorenbündel konstruiert: eines beruht auf den Indikatoren, Einkommen und Arbeitslosenquote von Absolventen, das zweite auf Aussagen, mit denen die Absolventen selbst ihre Diplome und Qualifikationen (6 Jahre nach dem Erwerb des Abschlusses) bewerten. Bei der Kombination dieser Indikatorenbündel ergaben sich erhebliche Unterschiede für den relativen Wert von Absolventen in den einzelnen Studienrichtungen, getrennt nach Geschlechtern. (IAB)
zwischen Bestimmung eines "Studienfachgleichgewichts" in der Hochschulbildung
Keywords: G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; L 2.3.2 Handlungs- & problemorientierte Methoden; G 2.5.4 Qualifizierungs- & Ausbildungskonzepte; G 1.3.3.1 Qualifikationsverwertung; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; P 2.1.5 Fachhochschul- und Hochschulreife; G 1.3.1 Bildungsangebot & -nachfrage; S 1.4 Hochschulbildung; G 1.2 Arbeitsmarkt; Hochschulpolitik; Arbeitskräftebedarf; Praxisbezug; Qualifikationsverwertung; Einkommen; Arbeitslosigkeit; Geschlechtsspezifische Faktoren; Hochschule; Absolvent; Bildungsnachfrage; Studienfach; Studienerfolg; Arbeitsmarktindikatoren; Quantitative Angaben